Structure‐cytotoxicity relationship for apoptotic inducers organotin(IV) derivatives of mandelic acid and L‐proline and their mixed ligand complexes having enhanced cytotoxicity. (11th December 2018) - Nath, Mala; Roy, Partha; Mishra, Rutusmita; Thakur, Mridula
Abstract : Structure‐cytotoxicity relationship of di−/tri‐organotin(IV) derivatives of mandelic acid (1 –4 ), L‐proline (5 –7, 15, 16 ), and mixed ligand complexes of latter with 1, 10‐phenanthroline (8 –14 ) investigated on the basis of MTT assay against human cancer cell lines, viz . MCF‐7 (mammary cancer), HepG2 (liver cancer) and PC‐3 (prostate cancer) in vitro indicated that all complexes except methyl‐ and octyl‐ analogues displayed potential cytotoxicity. The most active one is dibutyltin(IV) mandelate (2 ) exhibiting IC50 2.03 ± 0.40, 0.98 ± 0.23 and 3.86 ± 1.68 μM against MCF‐7, HepG2 and PC‐3, respectively, which is ≈ 15 and 2.5 times against MCF‐7, 20 and 5 times against HepG2 and 5 and ≈ 3 times against PC‐3 more cytotoxic than cis ‐platin and 5‐fluorouracil, respectively. Diorganotin(IV) derivatives of mandelic acid are more cytotoxic than triorganotin analogues. Organotin(IV) derivatives of L‐proline (except Bu3 Sn(Pro)16 ) are less cytotoxic than those of mandelic acid but their cytotoxicity is enhanced by complexion with 1, 10‐phenanthroline. This may be due to the structural planarity and extended π system of 1, 10‐phenanthroline which facilitates their transportation across the cell membrane and enhances the possibility of DNA intercalation over the planar L‐proline ring, and eventually, their DNA binding affinity so as to interfere with the cellular functions of DNA leading to apoptosis. Various biophysical experiments such as DNA fragmentation, acridine orange and comet assays, and flow cytometry assay using annexin V–fluorescein isothiocyanate (FITC) and propidium iodide (PI) have been carried out in order to ascertain their mode of action. The observed results indicated that the major cause of cancer cell death is apoptosis, but a minor role played by necrosis cannot be excluded. It is concluded on the basis of the observed results that the nature and number of organic groups bonded to tin as well as the nature of counter anions play an important role in determining the cytotoxicity of organotin(IV) compounds. Abstract : Structure‐cytotoxicity relationship of di‐/tri‐organotin(IV) derivatives of mandelic acid, L‐proline and mixed ligand complexes of latter with 1, 10 phenanthroline against MCF‐7, HepG2 and PC‐3 cancer cell lines indicated that diorganotins are more cytoactive than triorganotin analogues.